Increasing Public Awareness of the Role of Zakat in Realizing Social Justice and Sustainable Economic Growth towards the Golden Indonesia 2045 - Zionis, Rijal Mumazziq; Zunaidi, Arif; Natalina, Sri Anugrah; Rahmadanti, Utari; Laura, Tiffany Dewi; Fathurrokhim, Haedar (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service activity aims to increase the awareness of students of the Faculty of Islamic Economics and Business, IAIN Kediri, regarding the role of zakat in realizing social justice and sustainable economic growth. This national seminar was held on September 18, 2024, in the 4th Floor Hall of the IAIN Kediri Library, with a service learning approach. Through this method, participants not only receive theoretical material but are also encouraged to apply this understanding in real life. This activity includes the delivery of material from experts in zakat and Islamic economics, interactive discussions, and simulations of the application of productive zakat in the context of the local economy. It is hoped that this seminar can equip students with deeper knowledge and awareness of zakat as a strategic economic instrument that has the potential to encourage social justice and community welfare in a sustainable manner. This activity also aims to prepare students to contribute to realizing Indonesia Emas 2045 through the application of zakat values.